2014
DOI: 10.1377/hlthaff.2014.0280
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hospital Care Is The Chief Driver Of Regional Spending Variation In Medicare Patients With Advanced Cancer

Abstract: The root causes of regional variation in medical spending are poorly understood and vary by clinical condition. To identify drivers of regional spending variation for Medicare patients with advanced cancer, we used linked Surveillance, Epidemiology, and End Results (SEER) program–Medicare data from 2004–10. We broke down Medicare spending into thirteen cancer-relevant service categories. We then calculated the contribution of each category to spending and regional spending variation. Acute hospital care was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 26 publications
7
103
1
Order By: Relevance
“…Consistent with prior work 10,11 and to identify individuals diagnosed with cancer at stages for which treatment is typically palliative, 3,4 advanced stage was defined as stage IV for all cancers, stage IIIB for nonsmall-cell lung cancer (NSCLC), and stage III for pancreatic cancer (Appendix Table A1, online only). Data for individuals younger than 18 years old at diagnosis (n = 3), those who were missing or had duplicate variables needed for OSHPD linkage (n = 2,378), and those for whom date of death was missing or recorded as the same day as diagnosis (n = 58) were excluded.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with prior work 10,11 and to identify individuals diagnosed with cancer at stages for which treatment is typically palliative, 3,4 advanced stage was defined as stage IV for all cancers, stage IIIB for nonsmall-cell lung cancer (NSCLC), and stage III for pancreatic cancer (Appendix Table A1, online only). Data for individuals younger than 18 years old at diagnosis (n = 3), those who were missing or had duplicate variables needed for OSHPD linkage (n = 2,378), and those for whom date of death was missing or recorded as the same day as diagnosis (n = 58) were excluded.…”
Section: Samplementioning
confidence: 99%
“…Inpatient care drives regional variation in costs for advanced cancer care, which suggests that health system factors or local practice patterns, rather than clinical need alone, may drive care provision to some extent. 10 In addition, planned hospitalizations for individuals with advanced cancer may be considered potentially avoidable in cases for which improved communication about prognosis, advanced care planning, and Covariates included the following: age, sex, race/ethnicity, insurance status, marital status, area-based socioeconomic status quintile (SES), 28 and comorbidities (Table 1). Hospital characteristics, derived from the 2012 OSHPD Hospital Annual Utilization Report, included the following: hospital size, ownership type, presence of a teaching program, and presence of an outpatient palliative care program (described in the Appendix, online only).…”
Section: Outcomes and Variable Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease-and treatment-related morbidity leading to hospitalization is particularly relevant [5,6], given that inpatient admission is associated with reduced quality of life among patients with incurable cancer including glioblastoma [7,8], as well as growing calls to reduce readmissions from quality-of-care and costcontainment perspectives [9,10]. Prior studies have reported on treatment tolerance specifically in the elderly glioblastoma population [11][12][13][14], and randomized trials have profiled adverse events among patients eligible for clinical trial inclusion [2].…”
Section: Introductionmentioning
confidence: 99%
“…# Platelets <150 ×1,000/µL, GFR <60 mL/min, calcium <2.15 mg/dL, and white blood cell count <4.2 ×1000/µL predicted chemotherapy-related hospitalization in patients receiving palliative chemotherapy [12]. Color version available online patients with advanced cancer [25]. In this cohort, the hospitalization rate was high.…”
Section: Discussionmentioning
confidence: 84%